Prediction of Potential Acid Mine Drainage Formation in High Sulfidation Epithermal Deposit using Geochemical and Mineralogy Approaches - Syaputra, Rizky; Kusuma, Ginting Jalu; Badhurahman, Abie (BRIN Publishing, 2023)
Identification of acid mine drainage (AMD) can be predicted using a geochemical and mineralogy characterization approach to identify rocks forming and neutralizing acids. Geochemical characterization using static and kinetic tests. The static test is the first step to determining the potential for acid formation in rocks by comparing the potential for forming and neutralizing acids, which are characterized by uncertain behavior that causes predictions to be inaccurate. Kinetic tests were carried out to predict the long-term acid-producing potential better. Furthermore, mineralogical characterization is needed to assess the importance of sample mineral content in predicting AMD. Tests were conducted on rock samples from high sulfidation epithermal (HSE) deposits in North Sulawesi, Indonesia. The samples represent the different geological domain conditions found in HSE deposits. The main acid-producing components are pyrite and secondary minerals (alunite) capable of buffering acidity. The results showed a lower change in leachate pH (from day 30 to 180) and were accompanied by the release of species (high dissolved metals).